Autonomic Regulation during Quiet and Active Sleep States in Very Preterm Neonates - Reulecke, Sina; Schulz, Steffen; Voss, Andreas (Frontiers in Physiology, 2012)
The immature autonomic nervous system (ANS) in premature infants regulates heart rate (HR) and respiration different during quiet sleep (QS) and active sleep (AS). Little information is available about ANS regulation in these subjects. The aim of this study was to investigate changes in autonomic regulation and cardiorespiratory coupling during active and quiet sleep of 5 very preterm neonates with gestational age (GA) 26 - 31 weeks applying univariate and bivariate linear and nonlinear dynamics methods to the recorded cardiorespiratory signals. During QS univariate linear indices revealed lower standard deviations and entropies indicating decreased heart rate variability. More balanced sympatho-vagal behaviour of the ANS despite sympathetic activity was revealed by decreased low frequency (LF), increased high frequency (HF) and a lower ratio LF/HF in QS. Applied nonlinear indices (probabilities, entropies and fractal measures) quantifying the complexity and scaling behaviour of heart rate regulation processes were significantly altered in QS in comparison to AS. This reflects a lower short-term variability, less complexity, and a loss of fractal-like correlation properties of HR dynamics in QS. One major finding is that cardiorespiratory coupling is not yet completely developed in very preterm neonates with 26-31 weeks GA. Significantly different regulation patterns in bivariate oscillations of HR and respiration during AS and QS could be recognized. These patterns were characterized on the one hand by predominant monotonous regulating sequences originated from respiration independently from HR time series in AS and to a minor degree in QS and on the other hand by some prominent HR regulation sequences in QS independent of respiratory regulation. We speculate that these findings might be suitable for monitoring preterm neonates and for detecting disorders in the developing cardiorespiratory system.